How Do Persons Who Inject Drugs Experience Care From Nurses in Hospital Settings? A Qualitative Study - Kjerstine Solheim; Marit Hegg Reime; Leslie S. P. Eide (SAGE Publishing, 2024)
People who inject drugs (PWID) are at increased risk of acute and chronic health outcomes and in need of in-hospital healthcare services. This study aims to give insight into how PWID experience care from nurses in hospital settings. We used a qualitative descriptive design and applied reflexive thematic analysis to 11 individual semi-structured interviews with PWID. Our analysis generated the following main themes: (1) diminishment and distance-always just a drug addict, (2) gratitude-equal care not taken for granted, and (3) vulnerability-already carrying a heavy burden. Our findings reveal a complex, nuanced narrative regarding participants' experiences of nursing care and highlight the importance of enhancing knowledge, understanding, empathy, and communication skills when nurses encounter PWID. Our research suggests that patients' vulnerability resulting from previous experiences defined their perception of quality of care. Insight from this study provides valuable knowledge about how to enhance nursing care for PWID.